Nb-doped ultrahigh nickel ternary positive electrode material, preparation method thereof and lithium battery

By doping Nb and preparing ultra-high nickel ternary cathode materials, the challenges of traditional materials in cyclic stability and rate performance are solved, and higher stability and life can be achieved, as well as safe and stable operation at higher voltages.

CN119797448APending Publication Date: 2025-04-11SICHUAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510017264.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional ultra-high nickel ternary cathode materials have challenges in cycle stability and rate performance, such as capacity attenuation and short cycle life, limiting the performance and application range of lithium-ion batteries.

Method used

By doping Nb, the ultra-high nickel hydroxide precursor, lithium hydroxide and niobium oxide composites are mixed with preset molar ratios, and solid phase grinding and calcining are carried out to prepare the ultra-high nickel ternary cathode material Nb-LiNi0.92Co0.05Mn0.03O2 with Nb doped.

Benefits of technology

The material exhibits better stability and lifespan in long-term use, can maintain high performance during fast charging and discharging, and operates safely and stably at higher voltages, expands the application range, and improves the battery charge and discharge rate and effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797448A_ABST
    Figure CN119797448A_ABST
Patent Text Reader

Abstract

The invention provides a Nb-doped ultra-high nickel ternary positive electrode material, a preparation method thereof and a lithium battery, and the preparation method of the Nb-doped ultra-high nickel ternary positive electrode material comprises the following steps: 1, mixing an ultra-high nickel hydroxide precursor, lithium hydroxide and a niobium oxide compound according to a preset molar ratio, and carrying out solid-phase grinding on the mixture until the mixture is in a uniform state; and 2, calcining the ground mixture to obtain the Nb-doped ultrahigh-nickel ternary positive electrode material. The ultrahigh-nickel ternary positive electrode material obtained by the preparation method of the Nb-doped ultrahigh-nickel ternary positive electrode material provided by the invention shows better stability and longer service life in long-term use; relatively high performance can be maintained in a rapid charging and discharging process; the circuit can work safely and stably under higher voltage, and the application range is expanded; the charging and discharging rate and effect of the battery are improved; the structure is kept stable in the using process, and material degradation and performance reduction are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to a Nb-doped ultra-high nickel ternary positive electrode material, a preparation method thereof, and a lithium battery. Background Art

[0002] As the main energy storage device, lithium-ion batteries are increasingly popular in electric vehicles and renewable energy fields. Ultra-high nickel ternary cathode materials have become one of the research hotspots for lithium-ion battery cathode materials due to their high specific capacity and excellent electrochemical properties. However, traditional ultra-high nickel ternary materials have a series of challenges in cycle stability and rate performance, such as capacity decay and short cycle life, which limit the performance and application range of lithium-ion batteries.

[0003] Therefore, how to improve the electrochemical performance of ultra-high nickel ternary materials and enhance the stability of the ultra-high nickel ternary material structure has become a difficult problem that technicians in this field are concerned about. Summary of the invention

[0004] The object of the present invention is to provide a Nb-doped ultra-high nickel ternary positive electrode material and a preparation method thereof and a lithium battery to improve the above-mentioned problems.

[0005] In order to achieve the above purpose, the technical solution adopted by the embodiment of the present invention is as follows:

[0006] In a first aspect, an embodiment of the present invention provides a method for preparing a Nb-doped ultra-high nickel ternary positive electrode material, comprising the following steps:

[0007] Step 1: Mixing an ultra-high nickel hydroxide precursor, lithium hydroxide and a niobium oxide composite according to a preset molar ratio, and solid-phase grinding the mixture to a uniform state;

[0008] Step 2: Calcine the ground mixture to obtain the Nb-doped ultra-high nickel ternary positive electrode material Nb-LiNi 0.92 Co 0.05 Mn 0.03 O2.

[0009] In a second aspect, an embodiment of the present invention provides an ultra-high nickel ternary positive electrode material obtained by the above-mentioned method for preparing the ultra-high nickel ternary positive electrode material doped with Nb;

[0010] The secondary particles of the ultra-high nickel ternary positive electrode material are composed of long strip-shaped primary particles arranged radially.

[0011] In a third aspect, an embodiment of the present invention provides a lithium battery, comprising a positive electrode sheet prepared from the above-mentioned ultra-high nickel ternary positive electrode material.

[0012] Compared with the prior art, the embodiment of the present invention provides a Nb-doped ultra-high nickel ternary positive electrode material and a preparation method thereof and a lithium battery. The preparation method of the Nb-doped ultra-high nickel ternary positive electrode material comprises: step 1: mixing an ultra-high nickel hydroxide precursor, lithium hydroxide and a niobium oxide composite according to a preset molar ratio, and solid-phase grinding the mixture to a uniform state; step 2: calcining the ground mixture to obtain an ultra-high nickel ternary positive electrode material Nb-LiNi doped with Nb 0.92 Co 0.05 Mn 0.03 The ultra-high nickel ternary positive electrode material obtained by the preparation method of the ultra-high nickel ternary positive electrode material doped with Nb provided by the present invention exhibits better stability and life in long-term use; can maintain higher performance during rapid charge and discharge; can work safely and stably at higher voltages, expanding the scope of application; improves the battery charge and discharge rate and effect; maintains a stable structure during use, reducing material degradation and performance degradation.

[0013] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0015] Figure 1 Theoretical design of the modification roadmap of the Nb-doped ultra-high nickel ternary positive electrode material provided in the embodiment of the present invention.

[0016] Figure 2 A schematic diagram of the formation energy corresponding to the 1st, 2nd and 3rd layers of the Nb element in the Nb-doped ultra-high nickel ternary positive electrode material provided in an embodiment of the present invention.

[0017] Figure 3 XRD diagrams of all samples provided in the embodiments of the present invention.

[0018] Figure 4 This is one of the XRD local enlarged images of all samples provided in the embodiments of the present invention.

[0019] Figure 5 This is the second XRD partial enlarged image of all samples provided in the embodiments of the present invention.

[0020] Figure 6This is a graph of the XRD refinement results of the NCM9253 sample provided in an embodiment of the present invention.

[0021] Figure 7 This is a graph of the XRD refinement results of the Nb5-NCM9253 sample provided in an embodiment of the present invention.

[0022] Figure 8 This is a graph of the XRD refinement results of the Nb1-NCM9253 sample provided in an embodiment of the present invention.

[0023] Fig. 9 This is a graph of the XRD refinement results of the Nb15-NCM9253 sample provided in an embodiment of the present invention.

[0024] Fig.10 One of the first cycle charge and discharge curves of the batteries corresponding to all samples provided in the embodiments of the present invention.

[0025] Fig.11 One of the cycle performance graphs of the batteries corresponding to all samples provided in the embodiments of the present invention.

[0026] Fig.12 The second first cycle charge and discharge curve diagram of the batteries corresponding to all samples provided in the embodiments of the present invention.

[0027] Fig.13 The second graph of the cycle performance of the batteries corresponding to all samples provided in the embodiments of the present invention.

[0028] Fig.14 The figure is a rate performance diagram of the batteries corresponding to all samples provided in the embodiments of the present invention at different rates.

[0029] Fig.15 This is a SEM image of the NCM9253 sample provided in an embodiment of the present invention.

[0030] Fig.16 This is a SEM image of the Nb1-NCM9253 sample provided in an embodiment of the present invention.

[0031] Fig.17 This is a SEM image of a cross section of a NCM9253 sample provided in an embodiment of the present invention.

[0032] Fig.18 This is a SEM image of the cross section of the Nb1-NCM9253 sample provided in an embodiment of the present invention.

[0033] Fig.19 This is the EDS Mapping diagram of the NCM9253 sample provided in an embodiment of the present invention.

[0034] Fig. 20This is the EDS Mapping diagram of the Nb1-NCM9253 sample provided in an embodiment of the present invention.

[0035] Fig.21 This is an EDS Mapping diagram of the cross section of the Nb1-NCM9253 sample provided in an embodiment of the present invention.

[0036] Fig. 22 SEM images of the NCM9253 sample and the Nb1-NCM9253 sample provided in the embodiments of the present invention after 100 cycles. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0038] In order to improve the electrochemical properties of ultra-high nickel ternary materials and enhance the stability of the ultra-high nickel ternary material structure, the embodiments of the present invention provide a method for preparing an ultra-high nickel ternary positive electrode material doped with Nb, and a method and application for preparing an ultra-high nickel NCM material modified by niobium doping with a radially ordered structure, thereby achieving a significant improvement in the cycle stability and rate performance of the material, and providing a new solution for the performance and application of lithium-ion batteries. Please refer to the following for details.

[0039] The present invention proposes a method for preparing a Nb-doped ultra-high nickel ternary positive electrode material, comprising the following steps:

[0040] Step 1: Mix the ultra-high nickel hydroxide precursor, lithium hydroxide and niobium oxide composite according to a preset molar ratio, and solid-phase grind the mixture to a uniform state.

[0041] Optionally, the ultra-high nickel hydroxide precursor in step 1 is a precursor Ni 0.92 Co 0.05 Mn 0.03 (OH)2, the niobium oxide composite uses Nb2O5, and the preset molar ratio is 1: (1.01-1.05): (0.005-0.015).

[0042] The implementation process of step 1 is: the precursor Ni 0.92 Co 0.05 Mn 0.03 (OH)2, LiOH·H2O and Nb2O5 are mixed in a molar ratio of 1:(1.01-1.05):(0.005-0.015), and the mixture is solid-phase ground to a uniform state.

[0043] Furthermore, the precursor Ni in step 1 0.92 Co 0.05 Mn 0.03 The molar ratio of (OH)2, LiOH·H2O and Nb2O5 is 1:1.03:0.01.

[0044] It should be noted that there is no restriction on the grinding vessel, which can be but is not limited to a mortar, and there is no restriction on the grinding time, which can be but is not limited to 15 minutes.

[0045] Step 2: Calcine the ground mixture to obtain the Nb-doped ultra-high nickel ternary positive electrode material Nb-LiNi 0.92 Co 0.05 Mn 0.03 O2.

[0046] The ultra-high nickel ternary positive electrode material Nb-LiNi obtained in step 2 0.92 Co 0.05 Mn 0.03 The secondary particles of O2 are composed of long strip-shaped primary particles arranged radially.

[0047] The ultra-high nickel ternary positive electrode material obtained by the preparation method of the Nb-doped ultra-high nickel ternary positive electrode material provided by the present invention shows better stability and life in long-term use; can maintain higher performance during rapid charging and discharging; can work safely and stably at higher voltages, expanding the scope of application; improves the battery charging and discharging rate and effect; maintains a stable structure during use, reducing material degradation and performance decline.

[0048] In an optional embodiment, the process of calcining the ground mixture in step 2 includes: a first stage, a second stage, a third stage and a fourth stage, as follows.

[0049] In the first stage, oxygen is added to the calcination space so that the oxygen proportion in the calcination space is greater than or equal to the target proportion.

[0050] Among them, the target ratio is 99.99%.

[0051] Optionally, in the first stage of step 2, during the process of oxygenating the calcining space, the calcining space is kept at 30° C. (or room temperature). The calcining space can be the inner space of a roller kiln or the inner space of a tubular furnace. The duration of the first stage can be 30 minutes.

[0052] The nickel content in high-nickel ternary materials is high, and nickel ions are prone to change valence during the synthesis process. Pure oxygen atmosphere can ensure that the material has enough oxygen to participate in the reaction during the high-temperature synthesis process, so that the nickel ions can be stably maintained in a suitable valence state to form a good layered structure, which is beneficial to the electrochemical properties of the material and can ensure that the battery has good cycle stability and high specific capacity during the charge and discharge process. At the same time, preparation in a pure oxygen environment helps to improve the crystallinity of the material, reduce crystal defects, and thus improve the physical and chemical properties of the material. In the high-temperature synthesis process of high-nickel ternary materials, if there is insufficient oxygen, lattice oxygen will be precipitated. This is because the high nickel content reduces the stability of the crystal structure of the material. In a pure oxygen environment, the oxygen vacancies in the material can be replenished in time to maintain the balance of oxygen in the material structure, thereby inhibiting oxygen precipitation. Oxygen precipitation will cause changes in the structure of the material, such as defects such as cracks, which will affect the performance of the battery, including capacity attenuation, shortened life, and reduced safety. Therefore, a pure oxygen atmosphere is more important for reducing oxygen precipitation and maintaining the stability of the material structure.

[0053] When the oxygen ratio in the calcination space is greater than or equal to the target ratio, it means that it is currently in a pure oxygen atmosphere. Calcination at this time can inhibit the precursor Ni 0.92 Co 0.05 Mn 0.03 (OH)2 reacts with LiOH.

[0054] In the second stage, the calcination space is controlled to heat up to 470° C.-490° C. at a first rate, and pre-calcination is performed for 300 minutes.

[0055] The first rate may be, but is not limited to, 5°C / min, and the pre-calcination temperature may be 480°C.

[0056] Optionally, in the second stage of step 2, the calcination space is controlled to heat up to 480° C. at a first rate (5° C. / min).

[0057] The main purposes of pre-calcining high nickel ternary materials are as follows:

[0058] First, the crystal structure is initially formed. In the pre-calcination stage, the metal ions in the raw materials begin to arrange in order, laying the foundation for the subsequent formation of a complete high-nickel ternary material with a good layered structure, which is conducive to the improvement of the material's crystallinity.

[0059] Second, remove impurities. The pre-calcination process can volatilize some volatile impurities in the raw materials at a relatively low temperature, thereby improving the purity of the material. This can reduce the adverse effects of impurities on the electrochemical properties of the material, such as preventing the increase in battery self-discharge caused by impurities.

[0060] In high-nickel ternary materials, pre-calcination and Nb doping are related. Doping Nb in the pre-calcination stage can have a positive effect on the structure of the material. Nb can enter the lattice structure of the material. During high-temperature pre-calcination, Nb doping can inhibit cation mixing. Because the nickel content in high-nickel ternary materials is high, cation mixing is prone to occur, and the addition of Nb can partially replace the nickel position and stabilize the crystal structure. At the same time, pre-calcination after Nb doping can also reduce the lattice strain of the material and improve the structural stability of the material, which is beneficial to the subsequent calcination process and the final electrochemical properties of the material, such as improving the cycle life and rate performance of the battery.

[0061] In the third stage, the calcination space is controlled to heat up to 700° C.-800° C. at a second rate and maintained for 600 min-960 min.

[0062] Wherein, the second rate is 5°C / min.

[0063] Optionally, in the third stage of step 2, the calcination space is controlled to heat up to 740°C-760°C at a second rate (5°C / min). In the third stage, the temperature needs to be maintained at 740°C-760°C. If the temperature is too high, there will be too much residual Li, which will lead to performance degradation. If the temperature is too low, it will lead to Li embedding. The optimal temperature is 760°C.

[0064] In the fourth stage, the calcination space is controlled to cool to 160° C.-240° C. at the third rate, and then naturally cooled to room temperature.

[0065] The third rate may be, but is not limited to, 2.5°C / min.

[0066] In the preparation process of high-nickel ternary materials, a cooling rate that is too high or too low will have adverse effects. A cooling rate that is too high will cause thermal stress inside the material. This is because the cooling speed of the outer layer and the inner layer of the material is inconsistent, resulting in uneven shrinkage, which will produce defects such as cracks and destroy the integrity of the crystal structure. This will lead to poor electrochemical performance, such as reduced battery cycle stability and accelerated capacity decay during the charge and discharge cycle. In addition, too fast cooling is not conducive to the phase change process, and may produce a metastable phase structure, causing the physical and chemical properties of the material to deviate from expectations, affecting the conductivity, etc.

[0067] Too low a cooling rate will extend the preparation cycle and reduce production efficiency. At the same time, slow cooling may cause the material to stay in the high temperature stage for too long, resulting in excessive particle growth, reducing the material's specific surface area, reducing electrochemical activity, and affecting battery rate performance. In addition, it will increase the probability of adverse reactions between the material and the surrounding environment, reducing the purity and quality of the material.

[0068] Optionally, in the fourth stage of step 2, the calcination space is controlled to be cooled to 200° C. at a third rate (2.5° C. / min).

[0069] The present invention also provides an ultra-high nickel ternary positive electrode material obtained by the above-mentioned preparation method of the ultra-high nickel ternary positive electrode material doped with Nb, wherein the secondary particles of the ultra-high nickel ternary positive electrode material doped with Nb are composed of long strip-shaped radially arranged primary particles.

[0070] The present invention also provides a lithium battery, which includes a positive electrode sheet prepared from the above-mentioned ultra-high nickel ternary positive electrode material.

[0071] Specifically, the prepared modified ultra-high nickel ternary material is used as the positive electrode material. The modified ultra-high nickel ternary positive electrode material, acetylene black, and PVDF are made into a slurry in a ratio of 80:13:7 and evenly coated on aluminum foil. After the aluminum foil is dried in an oven at 120°C, it is cut into pole pieces with a diameter of 14mm. Metal lithium is used as the counter electrode and assembled into a button cell in a glove box. After that, a constant current charge and discharge test can be performed with a voltage range of 0-4.3V and a current density of 1C=18mAg -1 .

[0072] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0073] Example 1

[0074] (1) Ni 0.92 Co 0.05 Mn 0.03 (OH)2 and LiOH·H2O were mixed in a molar ratio of 1:0.03, and the mixture was solid-phase ground to a uniform state.

[0075] (2) oxygen is added to the calcination space so that the oxygen ratio in the calcination space is greater than or equal to the target ratio, so that the calcination space is in a pure oxygen (99.99%) atmosphere.

[0076] (3) The calcination space was heated to 480°C at a rate of 5°C / min and pre-calcination was performed for 300 min.

[0077] (4) The calcination space was heated to 760°C at a rate of 5°C / min and maintained for 900 min.

[0078] (5) The calcination space was cooled to 200°C at a rate of 2.5°C / min and then naturally cooled to room temperature.

[0079] The undoped Nb ultra-high nickel ternary positive electrode material obtained in Example 1 is a secondary particle composed of amorphous block-shaped primary particles.

[0080] Example 2

[0081] (1) Ni0.92 Co 0.05 Mn 0.03 (OH)2, LiOH·H2O and Nb2O5 were mixed in a molar ratio of 1:0.03:0.005, and the mixture was solid-phase ground to a uniform state.

[0082] (2) oxygen is added to the calcination space so that the oxygen ratio in the calcination space is greater than or equal to the target ratio, so that the calcination space is in a pure oxygen (99.99%) atmosphere.

[0083] (3) The calcination space was heated to 480°C at a rate of 5°C / min and pre-calcination was performed for 300 min.

[0084] (4) The calcination space was heated to 760°C at a rate of 5°C / min and maintained for 900 min.

[0085] (5) The calcination space was cooled to 200°C at a rate of 2.5°C / min and then naturally cooled to room temperature.

[0086] Example 3

[0087] (1) Ni 0.92 Co 0.05 Mn 0.03 (OH)2, LiOH·H2O and Nb2O5 were mixed in a molar ratio of 1:0.03:0.01, and the mixture was solid-phase ground to a uniform state.

[0088] (2) oxygen is added to the calcination space so that the oxygen ratio in the calcination space is greater than or equal to the target ratio, so that the calcination space is in a pure oxygen (99.99%) atmosphere.

[0089] (3) The calcination space was heated to 480°C at a rate of 5°C / min and pre-calcination was performed for 300 min.

[0090] (4) The calcination space was heated to 760°C at a rate of 5°C / min and maintained for 900 min.

[0091] (5) The calcination space was cooled to 200°C at a rate of 2.5°C / min and then naturally cooled to room temperature.

[0092] The experiment found that through niobium doping and radially ordered structure modification, the capacity retention rate of the material was improved from 71.2% to 102.6% after 100 cycles, and it exhibited a high specific capacity of 172.5 mAh·g^-1 at a 5C rate.

[0093] Example 4

[0094] (1) Ni0.92 Co 0.05 Mn 0.03 (OH)2, LiOH·H2O and Nb2O5 were mixed in a molar ratio of 1:0.03:0.015, and the mixture was solid-phase ground to a uniform state.

[0095] (2) oxygen is added to the calcination space so that the oxygen ratio in the calcination space is greater than or equal to the target ratio, so that the calcination space is in a pure oxygen (99.99%) atmosphere.

[0096] (3) The calcination space was heated to 480°C at a rate of 5°C / min and pre-calcination was performed for 300 min.

[0097] (4) The calcination space was heated to 760°C at a rate of 5°C / min and maintained for 900 min.

[0098] (5) The calcination space was cooled to 200°C at a rate of 2.5°C / min and then naturally cooled to room temperature.

[0099] Please refer to Figure 1 , Figure 1 Theoretical design of the modification route map of the ultra-high nickel ternary cathode material doped with Nb provided in the embodiment of the present invention. Schematic illustration of the Nb element being added to the surface, the first, second and third layers of the material respectively.

[0100] Please refer to Figure 2 , Figure 2 A schematic diagram of the formation energy corresponding to the 1st, 2nd and 3rd layers of the Nb element in the Nb-doped ultra-high nickel ternary positive electrode material provided in an embodiment of the present invention.

[0101] Please refer to Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Figure 3 XRD diagrams of all samples provided in the embodiments of the present invention; Figure 4 One of the XRD partial enlarged images of all samples provided in the embodiments of the present invention; Figure 5 The second XRD partial enlarged image of all samples provided in the embodiments of the present invention; Figure 6 The XRD refinement result diagram of the NCM9253 sample provided in the embodiment of the present invention; Figure 7 This is an XRD refinement result diagram of the Nb5-NCM9253 sample provided in an embodiment of the present invention; Figure 8 The XRD refinement result diagram of the Nb1-NCM9253 sample provided in the embodiment of the present invention; Fig. 9This is a graph of the XRD refinement results of the Nb15-NCM9253 sample provided in an embodiment of the present invention.

[0102] Among them, NCM9253 represents the ultra-high nickel ternary positive electrode material prepared based on Example 1; Nb5-NCM9253 (or N5-NCM9253) represents the ultra-high nickel ternary positive electrode material doped with Nb prepared based on Example 2; Nb1-NCM9253 (or N1-NCM9253) represents the ultra-high nickel ternary positive electrode material doped with Nb prepared based on Example 3; Nb15-NCM9253 (or N15-NCM9253) represents the ultra-high nickel ternary positive electrode material doped with Nb prepared based on Example 4, which will not be repeated hereafter.

[0103] Figure 3 This indicates that the characteristic peaks of all samples in the present invention are aligned with the XRD characteristic peaks of high-nickel layered oxides. Figure 4 and Figure 5 It shows that all samples have obvious split peaks, indicating that all samples have good layered structures. Figure 6 , 7 , 8 and 9 are the refined images of NCM9253, Nb5-NCM9253, Nb1-NCM9253 and Nb15-NCM9253 respectively. All samples have good coincidence and the error is much less than 10%, so the refined results are reliable.

[0104] The XRD refinement results of all samples are shown in Table 1.

[0105] Table 1

[0106]

[0107] Please refer to Fig.10 , Fig.10 One of the first cycle charge and discharge curves of the batteries corresponding to all samples provided in the embodiments of the present invention. Fig.10 The charge and discharge were completed at a rate of 0.1C and a cut-off voltage of 4.3V.

[0108] Please refer to Fig.11 , Fig.11 One of the cycle performance graphs of the batteries corresponding to all samples provided in the embodiments of the present invention. Fig.11 The charge and discharge are completed at a rate of 1C and a cut-off voltage of 4.3V.

[0109] Please refer to Fig.12 , Fig.12 The second first cycle charge and discharge curve diagram of the batteries corresponding to all samples provided in the embodiments of the present invention. Fig.12 The charge and discharge were completed at a rate of 0.1C and a cut-off voltage of 4.5V.

[0110] Please refer to Fig.13 , Fig.13 The second graph of the cycle performance of the batteries corresponding to all samples provided in the embodiments of the present invention. Fig.13 The charge and discharge are completed at a rate of 1C and a cut-off voltage of 4.5V.

[0111] Please refer to Fig.14 , Fig.14 The figure is a rate performance diagram of the batteries corresponding to all samples provided in the embodiments of the present invention at different rates.

[0112] Fig.10 It shows that the introduction of Nb leads to a partial loss of discharge specific capacity at 0.1C and 4.3V cut-off voltage; Fig.11 It shows that after 100 cycles at 1C rate and 4.3V cut-off voltage, the modified sample N1-NCM9253 has the highest cycle retention rate and the highest capacity. NCM9253 has the lowest cycle retention rate. Fig.12 It shows that at 0.1C rate and 4.5V high voltage, the discharge specific capacity of NCM9253 sample is higher than that of N1-NCM9253; Fig.13 It shows that at 1C rate and 4.5V cut-off voltage, the high-voltage cycling stability of N1-NCM9253 is stronger than that of NCM-9253. Fig.14 Figure 2 is the rate performance diagram of all samples. The results show that N1-NCM9253 has the best rate performance.

[0113] Please refer to Fig.15 , Fig.16 , Fig.17 as well as Fig.18 , Fig.15 The SEM image of the NCM9253 sample provided in the embodiment of the present invention; Fig.16 SEM image of the Nb1-NCM9253 sample provided in the embodiment of the present invention; Fig.17 The SEM image of the cross section of the NCM9253 sample provided in the embodiment of the present invention; Fig.18 This is a SEM image of the cross section of the Nb1-NCM9253 sample provided in an embodiment of the present invention.

[0114] Fig.15 and Fig.16 The comparison results show that the introduction of Nb element can refine the particle size of primary particles. Fig.17 and Fig.18 The results show that Nb can refine the grains and change the modified samples from secondary particle spheres formed by the accumulation of non-oriented primary particles to secondary particle spheres formed by the accumulation of slender and radially arranged primary particles.

[0115] Please refer to Fig.19 , Fig. 20as well as Fig.21 , Fig.19 EDS Mapping diagram of NCM9253 sample provided in the embodiment of the present invention; Fig. 20 EDS Mapping diagram of the Nb1-NCM9253 sample provided in an embodiment of the present invention; Fig.21 This is an EDS Mapping diagram of the cross section of the Nb1-NCM9253 sample provided in an embodiment of the present invention.

[0116] Fig.21 This indicates that the embodiment of the present invention successfully doped the Nb element into the bulk phase of the material.

[0117] Please refer to Fig. 22 , Fig. 22 SEM images of the NCM9253 sample and the Nb1-NCM9253 sample provided in the embodiments of the present invention after 100 cycles.

[0118] Fig. 22 This shows that the morphology of the N1-NCM9253 sample remains more complete after cycling under the same cycling conditions, so the structural stability of N1-NCM9253 is stronger than that of NCM9253.

[0119] In summary, the present invention provides a Nb-doped ultra-high nickel ternary positive electrode material, a preparation method thereof, and a lithium battery. The preparation method of the Nb-doped ultra-high nickel ternary positive electrode material comprises: step 1: mixing an ultra-high nickel hydroxide precursor, lithium hydroxide, and a niobium oxide composite according to a preset molar ratio, and solid-phase grinding the mixture to a uniform state; step 2: calcining the ground mixture to obtain an Nb-doped ultra-high nickel ternary positive electrode material Nb-LiNi 0.92 Co 0.05 Mn 0.03 The ultra-high nickel ternary positive electrode material obtained by the preparation method of the ultra-high nickel ternary positive electrode material doped with Nb provided by the present invention exhibits better stability and life in long-term use; can maintain higher performance during rapid charge and discharge; can work safely and stably at higher voltages, expanding the scope of application; improves the battery charge and discharge rate and effect; maintains a stable structure during use, reducing material degradation and performance degradation.

[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a Nb-doped ultra-high nickel ternary positive electrode material, characterized in that: The following steps are involved: Step 1: Mixing an ultra-high nickel hydroxide precursor, lithium hydroxide and a niobium oxide composite according to a preset molar ratio, and solid-phase grinding the mixture to a uniform state; Step 2: Calcine the ground mixture to obtain the Nb-doped ultra-high nickel ternary positive electrode material Nb-LiNi 0.92 Co 0.05 Mn 0.03 O2.

2. The method for preparing the Nb-doped ultra-high nickel ternary positive electrode material according to claim 1, characterized in that: The ultra-high nickel hydroxide precursor in step 1 is a precursor Ni 0.92 Co 0.05 Mn 0.03 (OH)2, niobium oxide composite uses Nb2O5, and the preset molar ratio is 1: (1.01-1.05): (0.005-0.015); The implementation process of step 1 is: the precursor Ni 0.92 Co 0.05 Mn 0.03 (OH)2, LiOH·H2O and Nb2O5 are mixed in a molar ratio of 1:(1.01-1.05):(0.005-0.015), and the mixture is solid-phase ground to a uniform state.

3. The method for preparing the Nb-doped ultra-high nickel ternary positive electrode material according to claim 2, characterized in that: Precursor Ni in step 1 0.92 Co 0.05 Mn 0.03 The molar ratio of (OH)2, LiOH·H2O and Nb2O5 is 1:1.03:0.

01.

4. The method for preparing the Nb-doped ultra-high nickel ternary positive electrode material according to claim 1, characterized in that: The process of calcining the ground mixture in step 2 comprises: In the first stage, oxygen is added to the calcination space so that the oxygen ratio in the calcination space is greater than or equal to the target ratio; In the second stage, the calcination space is controlled to heat up to 470° C.-490° C. at a first rate, and pre-calcination is performed for 300 minutes; In the third stage, the calcination space is controlled to heat up to 700° C.-800° C. at a second rate and maintained for 600 min-960 min; In the fourth stage, the calcination space is controlled to cool to 160° C.-240° C. at a third rate, and then naturally cooled to room temperature.

5. The method for preparing the Nb-doped ultra-high nickel ternary positive electrode material according to claim 4, characterized in that: In the third stage of step 2, the calcination space is controlled to heat up to 740° C.-760° C. at a second rate.

6. The method for preparing the Nb-doped ultra-high nickel ternary positive electrode material according to claim 4, characterized in that: The first rate and the second rate in step 2 are 5°C / min, and the third rate is 2.5°C / min.

7. The method for preparing the Nb-doped ultra-high nickel ternary positive electrode material according to claim 4, characterized in that: The target ratio in step 2 is 99.99%.

8. The method for preparing the Nb-doped ultra-high nickel ternary positive electrode material according to claim 4, characterized in that: In the first stage of step 2, the calcining space was maintained at 30° C. during the process of oxygenating the calcining space.

9. An ultra-high nickel ternary positive electrode material, characterized in that: Obtained by the preparation method of the Nb-doped ultra-high nickel ternary positive electrode material according to any one of claims 1 to 8; The secondary particles of the ultra-high nickel ternary positive electrode material are composed of long strip-shaped primary particles arranged radially.

10. A lithium battery, characterized in that: The lithium battery comprises a positive electrode sheet prepared from the ultra-high nickel ternary positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Preparation method of niobium-doped lithium nickel cobalt aluminate cathode material

    CN111653765A

  • Niobium phosphate coated niobium-doped high-nickel ternary positive electrode material and preparation method thereof

    CN113851633A

  • Lithium niobate coated and niobium doped coupled modified high-nickel ternary positive electrode material as well as preparation method and application of lithium niobate coated and niobium doped coupled modified high-nickel ternary positive electrode material

    CN114005984A

  • Lithium ion battery and preparation method thereof

    CN116885177A

  • Niobium-doped and lithium niobate-coated high-nickel positive electrode material as well as preparation method and application thereof

    CN118299560A